Uses of private health provider data for governance in low-income and middle-income countries: results from a scoping review - Faddoul, Alix; Montagu, Dominic; Kanneganti, Sneha; O’Hanlon, Barbara (BMJ open, 2024)
This work grew from an interest in understanding how private data are used for health system governance in low-income and middle-income countries (LMICs). - Objective We conducted a scoping review to understand how the public sector collects routine data from the private health sector and uses it for governance purposes. The private health sector was defined to include both formal and informal, for-profit or non-profit, actors delivering healthcare services. - Findings We identified 4014 individual English language studies published between 2010 and 2021. We reviewed titles and abstracts of all, with 50% reviewed by two authors to ensure a common application of inclusion criteria. 89 studies were selected for review in full; following this, 26 articles were included in the final selection as they directly report on the use of routine private sector data for governance in LMICs. Only English language studies were included, limiting the scope of possible conclusions. - Results Data were most commonly collected by the Ministry of Health or a subministerial office, with extraction from District Health Information System 2 specifically cited for three studies. 16 studies collected data on infrastructure and distribution, 15 on service delivery, 12 on health financing, 7 on pharmaceuticals and other consumables, 4 on health workforce, 4 on quality of care and 4 on epidemic surveillance. - Conclusion The studies identified provide examples of the public sector’s capacity to collect and use data routinely collected from the private sector to perform essential governance functions. The paucity of studies identified is an indication that more attention is needed to ensure that this key area of health system governance is undertaken and that lessons learnt are shared. This review provides insights to understanding private sector health data collection and use for governance in LMICs, and for guiding activities to assess and improve this according to country context and capacity.
Gesehen am 16.05.2025